ANALISIS FAKTORâFAKTOR YANG BERPENGARUH TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2013-2015) - Endah Setyo Anjarwati, 13.05.52.0047; Maryono, Maryono (Students Journal of Accounting and Banking, 2017)
This study aims to determine the effect of Audit Comitte, The Independent Commissioner, Other Public Shareholders, Profitability, and Size of Tax Avoidances at manufacture companies which listed in the Indonesia Stock Exchange. The population on this research is all manufacture company in the Indonesia Stock Exchange in 2013 - 2015. The sampling technique used was purposive sampling. The analytical tool was used is Multiple Regression Analysis. Partial results of this study show the Audit Comitte, The Independent Commissioner, Other Public Shareholders, Profitability of significant negative effect on tax avoidances while variable Size of significant positive affect the tax avoidances.Keywords: Audit Comitte, The Independent Commissioner, Other Public Shareholders, Profitability, and Size of Tax Avoidance